2005
DOI: 10.2139/ssrn.869451
|View full text |Cite
|
Sign up to set email alerts
|

The Practice Boundaries of Advanced Practice Nurses: An Economic and Legal Analysis

Abstract: The purpose of this study is to examine the causes and effects of State regulation that determines the extent of professional independence of advanced practice nurses (APNs). We analyze determinants of these regulations in panel data across States.We find that in States where APNs have acquired a substantial amount of professional independence, the earnings of APNs are substantially lower, and those of physicians' assistants are substantially higher, than in other States. These results are striking since physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
3
21
1
Order By: Relevance
“…Dueker et al [20] made an early contribution to this literature and found the unintuitive result that greater practice authority leads NPs to have lower incomes. Perry [21], using a richer data set in which NPs can be specifically identified, a shortcoming of Dueker et al work, finds that NPs who are granted greater practice authority experience significant increases in their incomes relative to NPs who are not granted greater practice authority.…”
Section: Introductionmentioning
confidence: 99%
“…Dueker et al [20] made an early contribution to this literature and found the unintuitive result that greater practice authority leads NPs to have lower incomes. Perry [21], using a richer data set in which NPs can be specifically identified, a shortcoming of Dueker et al work, finds that NPs who are granted greater practice authority experience significant increases in their incomes relative to NPs who are not granted greater practice authority.…”
Section: Introductionmentioning
confidence: 99%
“…to provide care and may impose costs on these providers in at least four ways (see Kleiner et al 2016): (1) physician supervision requirements tether NPs and PAs to their supervising physicians and may limit their ability to provide care in locations that are convenient for consumers, in rural or isolated areas, or in other settings where physicians have historically been unwilling to practice; (2) physicians may be unwilling or unable to supervise NPs and PAs in certain areas, limiting the ability of NPs and PAs to practice in these areas; 14 (3) supervision laws impose administrative burdens and other costs on NPs and PAs; and/or (4) supervision laws may effect a monetary transfer from NPs and PAs to physicians (see, e.g, Perry 2009;Dueker et al 2005;Kleiner et al 2016;Gilman & Koslov 2014). In general, I expect that relaxing these requirements will have a larger effect on NP supply than on PA supply for two reasons: PAs are tied more closely to their supervising physicians than NPs, and the marginal change from one level of supervision to another is smaller for PAs than NPs-unlike NPs, PAs can never practice independently.…”
Section: A Occupational Licensing Lawsmentioning
confidence: 99%
“…In a literature review, only two studies focusing on the effect of SOP reforms on physician and nurse income were identified [9, 10]. Dueker et al used information from the current population survey (CPS) from 1988 to 2002 for earnings data for APRNs, physician assistants (PAs), and physicians (MDs).…”
Section: Previous Researchmentioning
confidence: 99%